Use of acoustic energy in sand casting of aluminium alloys - Puga, Hélder (2013)
During the last years, some researchers have focused the development of ultrasonic microstructure refinement /modification techniques of die-casting aluminium alloys, to improve their properties. The developed techniques are highly efficient when applied to the die-casting process, but their capability with sand and ceramic moulding are unknown. Sand/ceramic aluminium castings are prone to coarse microstructure, porosities and inclusions due to low cooling rates and turbulent gravity pouring, and suitable processing techniques are required to eliminate those drawbacks. This article reports some results of a research work aiming the development of a reliable, low-cost and environmentally friend casting process, for geometrically complex and massive high strength sand/ceramic aluminium castings, to eliminate traditional soundness related defects and simultaneously promote the development of refined microstructures. The article presents the effect of applying ultrasound to AlSi9Cu3 alloy during solidification on a sand mould on the resultant microstructure. Results include microstructure characterization and its relationship with thermal analysis data collected from the center of the cast samples during cooling.